Long‐Term and Regional‐Scale Data Reveal Divergent Trends of Different Climate Variables on Fish Body Size Over 75 Years - Peter J. Flood; Kaitlin E. Schiller; Katelyn B. S. King; Andrew D. Runyon; Kevin E. Wehrly; Karen M. Alofs (Global Change Biology, 2025)
Across many ecto‐ and endothermic organisms, climate change has induced a general shift towards smaller body sizes. Several existing hypotheses (e.g., Temperature Size Rule—TSR, metabolic theory) contribute to our understanding of climate‐driven changes in body size. However, empirical support for climate‐induced reductions in body size is mixed with some species growing larger under warmer temperatures, and underlying mechanisms are under debate. To address these inconsistencies, we used Bayesian hierarchical modeling to determine if mean length‐at‐age (proxy for growth) changed from 1945 to 2020 for age classes of 13 freshwater fish species. Then, we used boosted regression trees (BRTs) to disentangle the impacts of climate change on growth from other environmental factors. Hierarchical modeling revealed that 37% of age classes were decreasing in mean length through time (69% were qualitatively decreasing). BRTs demonstrated that growing degree days and mean annual surface water temperature had varying effects on growth. For cold‐and cool‐water adapted fishes, length‐at‐age usually increased as a function of degree days but decreased as a function of surface temperature. Warm‐water adapted fishes, however, typically decreased in response to both degree days and surface temperature. The direction of change in length‐at‐age as a function of surface temperature corresponded to the direction of change over time for 62% (8/13) of species. Overall, we found widespread decreases in length, including age classes from all thermal guilds and juveniles (contrary to TSR assumptions). Mixed results in prior literature may result from choosing different variables to represent climate warming and/or not considering age‐specific length responses. When specific climate variables and age are considered, climate change effects on body size may be more predictable at large temporal and spatial scales than previously thought. Continued decreases in length for the youngest and oldest fishes could lead to biodiversity loss and diminished ecosystem functions and services.